Contratações temporárias de excepcional interesse público : análise dos processos seletivos simplificados no estado de Sergipe - Maia, Luiz Gustavo Esmeraldo Gurgel (2021)
This research aimed to analyze temporary contracts for exceptional public interest, carried out through simplified selection processes, between the years 2016 and 2020 by municipalities in the State of Sergipe, to verify whether they complied with legal and constitutional requirements. In this sense, it started from the constitutional and legal premises related to the matter, to delimit the conceptual boundaries and corroborate that, under the current legal system, the public tender is the rule that should govern the hiring of public servants and employees (art. 37 , II, of the Federal Constitution). However, this rule has exceptions, among which temporary hiring stands out, revealed as a legal-administrative link between this public agent and the contracting entity. Dealing with the guidelines that regulate this type of contracting of a peculiar nature, the study discusses the need for a specific legal provision in the entity, the demonstration of the real exceptional situation of temporary public interest, the realization of a simplified selection process able to safeguard transparency, honesty and impersonality in the selections, as well as listing the main related legislation, with mandatory observance, on the matter. Methodologically, this descriptive research indicates, based on a diagnosis based on bibliographic and documentary analysis, irregularities present in temporary contracts of exceptional public interest in the municipalities of the State of Sergipe between the years 2016 and 2020. The nature of the problem uses the mixed methodology (qualitative and quantitative), with the purpose of applied research, and the case study as a method of procedure. Thus, from the metric used, it was shown that the simplified selection processes analyzed reached just over half of the ideal score according to the legislation, especially in relation to non-compliance with constitutional provisions regarding the nature of the positions that are available, the absence of demonstration of the exceptional public interest and justification in hiring, as well as disrespect for the personnel ceiling provided for in the LRF. Thus, the results collected with the case study subsidized the edition of regulations containing the necessary requirements for such contracts, whose replication can be done by other external control units throughout the country.